TI_GERICHTE 35.2020.63 vom 5. Juli 2021 , Discussa la stabilizzazione dello stato di salute e il diritto a una rendita d'invalidità - TI Tribunale d'appello (2021)
Discussa la stabilizzazione dello stato di salute e il diritto a una rendita d'invalidità